Enhancing education through community engagement: Perspectives of student volunteers - C M Kell; F Haffejee; J F Ducray (South African Medical Association, 2023)
Background. Engagement between higher education institutions and underprivileged communities holds valuable potential for mutual benefit. In a country of vast inequalities such as South Africa (SA), community engagement also has the potential, via health promotion of local communities, to alleviate some of the burden placed on the public healthcare system, while simultaneously strengthening the personal and professional development of student participants. Objective. To explore the experiences, perceptions and insights of student volunteers (SVs) who assisted with a collaborative health-promotion project. Methods. This qualitative study used thematic analysis of semi-structured interviews to explore the experiences of six SVs in the Faculty of Health Sciences, Durban University of Technology, SA, who assisted in educating local vulnerable women on various aspects of female reproductive health at a wellness day for such women. Results. The SVs described the experience as positive and humbling, enhancing their professional and personal development. They reported that the community engagement helped them to define themselves and to grow skills they will need as future practitioners. The exposure to the challenges faced by vulnerable groups helped them to develop a sense of empathy and compassion, while igniting an eagerness to empower these groups through improved health literacy. Conclusion. The insights provided by this qualitative exploration strongly support the use of community engagement to develop culturally sensitive, empathetic healthcare practitioners.